Dermatological manifestations in Noonan syndrome: a prospective multicentric study of 129 patients positive for mutation3. (18th January 2019) - Bessis, D.; Miquel, J.; Bourrat, E.; Chiaverini, C.; Morice‐Picard, F.; Abadie, C.; Manna, F.; Baumann, C.; Best, M.; Blanchet, P.; Bursztejn, A.‐C.; Capri, Y.; et al.
Summary: Background: Data on dermatological manifestations of Noonan syndrome (NS) remain heterogeneous and are based on limited dermatological expertise. Objectives: To describe the dermatological manifestations of NS, compare them with the literature findings, and test for dermatological phenotype–genotype correlations with or without the presence of PTPN11 mutations. Methods: We performed a large 4‐year, prospective, multicentric, collaborative dermatological and genetic study. Results: Overall, 129 patients with NS were enrolled, including 65 patients with PTPN11 ‐NS, 34 patients with PTPN11 ‐NS with multiple lentigines (NSML), and 30 patients with NS who had a mutation other than PTPN11 . Easy bruising was the most frequent dermatological finding in PTPN11 ‐NS, present in 53·8% of patients. Multiple lentigines and café‐au‐lait macules ( n ≥ 3) were present in 94% and 80% of cases of NSML linked to specific mutations of PTPN11, respectively. Atypical forms of NSML could be associated with NS with RAF1 or NRAS mutations. In univariate analysis, patients without a PTPN11 mutation showed (i) a significantly higher frequency of keratinization disorders ( P = 0·001), including keratosis pilaris ( P = 0·005), ulerythema ophryogenes ( P = 0·0001) and palmar and/or plantar hyperkeratosis ( P = 0·06, trend association), and (ii) a significantly higher frequency of scarce scalp hair ( P = 0·035) and scarce or absent eyelashes ( P = 0·06, trend association) than those with PTPN11 mutations. Conclusions: The cutaneous phenotype of NS with a PTPN11 mutation is generally mild and nonspecific, whereas the absence of a PTPN11 mutation is associated with a high frequency of keratinization disorders and hair abnormalities. Abstract : What's already known about this topic? Data on dermatological manifestations of Noonan syndrome (NS) remain heterogeneous and almost entirely without expert dermatological input. A broad spectrum of dermatological findings is present in NS and better knowledge might help to define phenotype–genotype correlations and differentiate forms of NS from other RASopathies, specifically cardiofaciocutaneous syndrome. What does this study add? NS with PTPN11 mutations is usually associated with a mild and nonspecific cutaneous phenotype. NS with multiple lentigines is typically associated with specific mutations of PTPN11 but atypical forms can be linked to RAF1 or NRAS mutations. Absence of PTPN11 mutation in NS is associated with a higher frequency of keratinization disorders and hair abnormalities, the latter being commonly observed in cardiofaciocutaneous syndrome. What is the translational message? Abnormalities of the genes of the Ras–MAPK signalling pathway that are involved in NS underlie a spectrum of cutaneous manifestations including hair abnormalities, keratinization, pigmentary and connective tissue disorders and multiple melanocytic naevi. This study adds new information to improve the definition of the cutaneous phenotype of NS and differentiate it phenotypically from RASopathies, specifically cardiofaciocutaneous syndrome and Costello syndrome. Linked Comment:  Carcavilla. Br J Dermatol 2019;180 :1293 . Plain language summary available online Respond to this article